Caudal regression syndrome with vestigial tail and esophageal duplication cyst - Mandal, Subinay; Hembram, Debasish (Journal of Pediatric Neurology, 2010)
Caudal dysgenesis constitutes a heterogeneous spectrum of congenital caudal anomalies, including varying degrees of developmental defects of the vertebral column, as well as anorectal and genitourinary anomalies. Herein, we are reporting a case of caudal regression syndrome with imperforate anus, bilateral renal hypoplasia, vestigial tail and esophageal duplication cyst in a baby of non-diabetic mother,
Keywords: Caudal regression syndrome; congenital anomaly; sirenomelia; vestigial tail